Assessment of turf quality in Paspalum vaginatum Sw. accessions of Sumatra, Java, and Bali (Indonesia) with clay and amended sand growing media - RAHAYU RAHAYU; DWI PRIYO ARIYANTO; AVIDA HANA USROTIN; FAISAL REZA HATAMI; YANG GEUN MO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rahayu, Ariyanto DP, Usrotin AH, Hatami FR, Mo YG. 2023. Assessment of turf quality in Paspalum vaginatum Sw. accessions of Sumatra, Java, and Bali (Indonesia) with clay and amended sand growing media. Biodiversitas 24: 1650-1658. Seashore paspalum (Paspalum vaginatum Sw.) is a selected turfgrass species in the FIFA football world cup Qatar 2022. The choice considers its turf quality, growth habit, quick recovery from damage, tolerance in warm conditions, and low water consumption. Since the breeding program of seashore paspalum worldwide still needs to be improved and is yet to start in Indonesia, we suppose that in the future, seashore paspalum will become a favorite turfgrass industry. Previous studies showed that Indonesia has many accessions to the germplasm of seashore paspalum. This study aimed to find superior mother lines of Indonesian germplasm accession by select of visual and functional quality using clay soil of vertisol and vertisol-amended sand as growing media for quality evaluation. This study was a wild-type collection followed by a plot experiment using Randomized Complete Block Design. In this experiment, the control was using a commercialized cultivar. Seashore paspalum accessions were collected from Java, Bali, and Sumatra Indonesian islands. Observation of variables were visual qualities, i.e., tiller density, color, leaf texture, uniformity, and functional quality, i.e., surface covering, recoverability, clippings dry weight, root length, root dry weight. The National Turfgrass Evaluation Program (NTEP) rated those qualities by scoring. The quality index of turfgrass used a rating score formulated from a visual and functional quality score. The data were analyzed using DMRT and T-test. Results showed that growing paspalum in clay-amended sand media showed a better recovery rate than the accessions grown in vertisol media. Mowing the grass can reduce plant height and leaf texture, and increases the clipping dry weight. Sand amendment to vertisol soil can improve the seashore paspalum visual qualities, i.e., leaf texture, tiller density, color score, and functional quality, such as root length. Seashore paspalum accessions vary in quality, i.e., visual and functional. Native accessions have a better recovery rate, higher tiller density, and uniformity than the control but a higher clipping yield. Bogor accession had faster soil surface coverage, Siak accession had a high recovery rate. Rumbei accession was the highest clipping dry weight, fast land cover, and high root dry weight. The accessions of Siak and Rumbei have higher quality index than the control after mowing. Siak accession performed better in vertisol, whereas Rumbei accession performed better in vertisol-amended sand. The performance of Rumbai and Siak accessions showed that seashore paspalum from Sumatra has better characteristics than Java and Bali and is promising for further cultivar development.